Validasi Metode Pendugaan Umur Simpan Produk Pangan Renyah dengan Metode Kadar Air Kritis - Novi Alfiyani; Nur Wulandari; Dede R. Adawiyah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
Abstract. Shelf life of food products is one of the most important information listed on food packaging labels. A dry crisp food product has a relatively long shelf life with sogginess as damage parameters. This research is aimed to obtain a validated procedure for shelf life estimation of dry crisp food products by critical moisture content method, so it can be used as a standard procedure in shelf life estimation. The research was conducted with seven repetitions by using potato chips as food model and it started by determination of initial moisture content, critical moisture content, weight of dry food solids, other variables, and determination of MSI curve of GAB model to obtain slope b and equilibrium moisture content. Shelf life was calculated by using Labuza’s Equation, then shelf life data obtained and the parameters affecting it, were validated by using precision criteria based on Relative Standard Deviation (RSD) less than 2/3 RSDH (Horwitz equation) value. The result showed that both of shelf life data and all affecting parameters, has been validated. Shelf life at 75 and 80% RH were 22.21±0.08 months and 11.44±0.08 months, RSD value were 0.37 and 0.74%, as well as 2/3 RSDH value were 0.84 and 0.92% respectively. Thus, it can be concluded that procedure of shelf life estimation of dry crisp food products by using critical moisture content method was a valid and an appropriate method for its purpose, and can produce accurate shelf life calculation. Keywords: critical moisture content method, dry crisp food product, Labuza’s equation, method validation, shelf life DOI: https://doi.org/10.29244/jmpi.2019.6.1.1